A PRAGMATIC ANALYSIS OF DIRECTIVE UTTERENCE USED BY ENGLISH TEACHER AT MADRASAH ALIYAH PONDOK PESANTREN AL-KAMIL - Mohammad Rizky Aziz; Moh Iqbal Firdaus; Aris Gumilar (Globish: An English-Indonesian Journal for English, Education, and Culture, 2021)
This research was intended to describe types of speech acts performed by English lecturers in learning process at Madrasah Aliyah Pondok Pesantren Al-Kamil. This research was descriptive qualitative. The data of this research were the English utterances performed by English Teachers. The researcher obtained the data by means of observation technique. In observation technique the researcher used recording instruments, sound recorder, to record the classroom dialogues. Next, the researcher writes some data into note to as a additional data report The researcher analyzes the directive speech act in this research using Kreidler’s theory (1998). Based on the observation, the researcher found three types of directive speech act. They are command/order, request, Warning or prohibitation. In conclusion, the researcher found directives speech act from observation are 3 utterances are command/order (2,80%) , 2 utterances are requesting (1,87%), 1 utterance is warning (0,93%), and 101 utterances are unidentified (94,39%)